Phyllodes tumor of the breast: Diagnosis,management and outcome during a 10-year experience - Chagkrit Ditsatham (2020)
© 2019 Ditsatham and Chongruksut. Background: Phyllodes tumor is a very rare tumor of the breast, incidence being 0.3–0.9% of all breast tumors. Phyllodes tumors are classified into three grades: benign, borderline or malignant. The aim of this study was to investigate patient characteristics, imaging characteristic findings, surgical treatment and outcome of phyllodes tumor. Materials and methods: This is a retrospective review of phyllodes tumor patients who had undergone surgical management between 1 January 2006 and 31 December 2015 in Head, Neck and Breast Unit, Department of Surgery, Chiang Mai University Hospital. Results: A total of 188 phyllodes tumor patients were included in this study. The average age of the patients was 35.6 years. The majority of the tumors were of lobulated shape. Tumor morphology from imaging: lobulated shaped tumor 112 cases, oval-shape 37 cases, round shape 8 cases and irregular 5 cases. Surgical management is the standard procedure for treatment of phyllodes tumors. A wide local excision was performed in 147 cases, mastectomy in 20 cases (modified radical mastectomy in 2 cases) and wide excision followed by mastectomy 21 cases. The final pathological diagnoses of the phyllodes tumors were: benign 118 cases (62%), borderline 33 cases (18%) and malignant in 37 cases (20%). The margin did not affect recurrence in all types. Conclusion: The most frequent is a benign phyllodes tumor. Surgical treatment to remove the tumor with a free margin is acceptable with no recurrence difference from a wider margin. However, younger age and malignant phyllodes tumor are the two highest risk factors for recurrence.